Supplemental feeding of birds in human settlements of western Poland - Chosińska, Karolina; Duduś, Leszek; Jakubiec, Zbigniew (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
Humans are probably the only species which obtain satisfaction from helping other species, including the feeding of animals. Since the end of the XIX century it has been proposed to feed birds, but only in the recent decades - due to the massive growth of urban populations with an accompanying increase of the urban areas and the synanthropisation and urbanisation of many animal species - bird feeding became more common and can be conducted throughout the year.
Keywords: birds; supplemental feeding; human settlements